PUBLIC HEALTH INTERVENTIONS FOR ORAL HEALTH IN RURAL SCHOOLS IN SRI LANKA (Proceedings of the International Conference on Public Health, 2023)
Dental caries and periodontal disease are common among the school children in rural areas. It is highly prevalent and become a “silent epidemic”. According to national oral health survey 2002-2003, 39.17% of 12 years have caries and in rural area it is 40.68%.  In the fight against dental caries Ministry of health has introduced “Save the Molar” project where fissure sealant is applied in schoolchildren by school dental therapists. As fissure sealant was a new introduction to the government system, the study aims to assess the retention of fissure sealant applied by SDT. Six SDT were selected from a rural district in Sri Lanka and they were trained for 2 days on selection of children and application of glass ionomer fissure sealant. Three of them had applied glass iomoner based fissure sealant in a mobile setup while the other three had applied the same fissure sealant in the school dental clinics. After a period of six months, the fissure sealants were reviewed to see whether they are fully intact, broken or completely dislodged. All the children were between ages 9-11.76.84% of the fissure sealant was present in the molar teeth after six months and 11.33% were broken and 11.82% were and completely dislodged from the teeth. In clinic setup 75.61% fully intact fissure sealant while 12.68% and11.70% were broken or completely dislodged respectively. However, in mobile setup results were much better, 79% of the fissure sealants were intact while 8.95% and 11.94% are either broken or dislodged respectively.This study shows no much difference in retention of glass ionomer fissure sealant applied in clinic setup and mobile setup. Overall retention percentages are high.
Keywords: dental caries; rural school